Patterns and surgical outcome of neonatal small bowel obstruction: a single center experience from Ujjain, India - Agarwal, Nitin; Agarwal, Deepika; Pathak, Deepali; Pathak, Ashish (International Surgery Journal, 2019)
Background: Neonatal small bowel obstruction is the most commonly encountered paediatric surgical emergency worldwide and in India. The objective of this study was to study the prevalence and spectrum of neonatal small bowel obstruction. Methods: A retrospective chart review of all neonates aged between 1-28 days that underwent surgery for small intestinal obstruction between January 2017 to January 2019 at Department of Paediatric Surgery, R.D. Gardi Medical College, Ujjain, MP. A predesigned questionnaire was used to collect demographic, clinical and outcome related information. Exploratory laparotomy and type of surgical intervention was done as per the cause. Results: A total of 52 neonates (M: F ratio 1.74: 1) were included in the study. The most common clinical features were vomiting (92%), bilious vomiting (85%) and abdominal fullness (75%) and laboratory feature was leucocytosis (42%) and thrombocytopenia (31%). Most (66%) neonates presented between 2-7 days and belonged to rural areas (65%). The two most common final diagnosis were malrotation (56%) and intestinal atresia (23%). Associated anomalies were seen in 29% [vertebral defects, anal atresia, cardiac defects, tracheo-esophageal fistula, renal anomalies, and limb abnormalities association (8%) and congenital heart disease (8%)]. The mean (±SD) duration to reach full feeds and duration of neonatal intensive care unit stay was 6.2±1.3 and 14.1 (±5) days, respectively. Complications were seen in 20% cases, most common being early bowel obstruction. A total of 6 (11.5%) neonates died in the post-operative period, 83% because of sepsis. Conclusions: Small bowel obstruction is common neonatal surgical emergency. Most common cause is malrotation and intestinal atresia. Neonatal sepsis is the most common underlying cause of death post-operatively.